An aerogel obtained from chemo-enzymatically oxidized fenugreek galactomannans as a versatile delivery system. (25th June 2016) - Rossi, Bianca; Campia, Paola; Merlini, Luca; Brasca, Milena; Pastori, Nadia; Farris, Stefano; Melone, Lucio; Punta, Carlo; Galante, Yves M.
Highlights: An aerogel was obtained by lyophilization of TEMPO-mediated, laccase-oxidized fenugreek galactomannans. The aerogel (referred to as EOLFG) is capable of water and solvent uptake over 20-folds its own weight. It was characterized by several spectroscopic techniques and its mechanical properties were measured. As a model system, lysozyme was shown to be entrapped and released from EOLFG in an active form. This biomaterial could find applications as a versatile delivery system of active principles in food, industrial and biomedical fields. Abstract: We describe a new aerogel obtained from laccase-oxidized galactomannans of the leguminous plant fenugreek ( Trigonella foenum-graecum ) and suggest its potential practical use. Laccase/TEMPO oxidation of fenugreek in aqueous solution caused a viscosity increase of over 15-fold. A structured, elastic, stable hydrogel was generated, due to formation of carbonyl groups from primary OH of galactose side units and subsequent establishment of hemiacetalic bonds with available free hydroxyl groups. Upon lyophilization of this hydrogel, a water-insoluble aerogel was obtained (EOLFG), capable of uptaking aqueous or organic solvents over 20 times its own weight. The material was characterized by scanning electron microscopy, FT-IR, elemental analysis and 13 C CP-MAS NMR spectroscopy and its mechanical properties were investigated. To test the EOLFG as a delivery system, the anti-microbial enzyme lysozyme was used as model active principle. Lysozyme was added before or after formation of the aerogel, entrapped or absorbed in the gel, retained and released in active form, as proven by its hydrolytic glycosidase activity on lyophilized Micrococcus lysodeikticus cells wall peptidoglycans. This new biomaterial, composed of a chemo-enzymatically modified plant polysaccharide, might represent a versatile, biocompatible "delivery system" of active principles in food and non-food products.